Development of Sparkol Vedio Scribe Assisted Learning Media - Fitri Nurrohmah; Fredi Ganda Putra; Farida Farida (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This study aims at how to develop sparkol video scribe assisted mathematics learning media and produce valid, practical, effective and responsive media. To achieve this goal the authors develop the media using research development methods with steps: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. Subjects in this study were students of the University of Islam Raden Intan Lampung with data collection instruments used in the form of a questionnaire given to the material experts, media experts, and questionnaire responses to students to know the interest of learning media developed mathematics. The results of this study produce a product in the form of sparkol video scribe-assisted mathematics learning media on assignment material (linear program) in higher education; knowing the feasibility of the developed product quality is very feasible with a score of 83,7% based on expert material judgment and 91,5% by the media expert in a very feasible category. Students' responses in sparkol video scribe assisted instructional media on assignment material (linear program) obtained a score of 83,2% with very interesting criteria in college. based on the suggestions from material experts and media experts to the author to be disseminated to lecturers for use in the learning process.